Neonatal reticulocyte count during the early postnatal period - Mika Yamada; Mina Chishiki; Yuji Kanai; Aya Goto; Takashi Imamura (Elsevier, 2020)
Background: There are few reports on reticulocyte count during the early postnatal period, and its clinical significance is not well understood. To examine the relationships between neonatal reticulocyte count and other perinatal variables. Methods: We conducted a retrospective cohort study of neonatal infants who were admitted to the neonatal intensive care unit (NICU) of Ohta Nishinouchi Hospital, Japan, between April 1, 2016 and July 31, 2019. All blood samples were collected within 3 h after admission. Results: Four hundred and twenty-eight infants were included, of whom 317 (74.1%) were preterm and 111 (25.9%) were term. Two hundred and ninety-nine infants (69.9%) were born by cesarean section. The median reticulocyte counts (‰) for all gestational ages (GAs) were as follows: 24-25 wks (n = 11), 124.1 (range: 106.3 to 148.6); 26-27 wks (n = 25), 111.1 (range: 55.5 to 144.3); 28-30 wks (n = 52), 81.9 (range: 35.6 to 131.5); 31-33 wks (n = 86), 71.6 (range: 28.3 to 116.6); 34-36 wks (n = 143); 59.6 (range: 30.2 to 110.9); and 37-41 wks (n = 111), 43.2 (range: 21.9 to 69.2). There were significant relationships between the neonatal reticulocyte count and gender [p < 0.01, odds ratio (OR), 0.37; 95% confidence interval (CI), 0.21 to 0.64], GA (p < 0.01, OR, 0.92; 95% CI, 0.90 to 0.93), delivery type (p = 0.03, OR, 0.51; 95% CI, 0.28 to 0.95), maternal haemoglobin before delivery (p < 0.01, OR, 0.74; 95% CI, 0.60 to 0.91), tracheal intubation at resuscitation (p = 0.04, OR, 2.75; 95% CI, 1.04 to 7.32) and mean platelet volume (p < 0.01, OR, 0.51; 95% CI, 0.35 to 0.74). Conclusion: A higher neonatal reticulocyte count in NICU infants may be one of the physiological responses to a more rapid environmental change during the early postnatal period.